2016
DOI: 10.4103/1947-2714.183012
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and histomorphometric investigation of bisphenol a and nonylphenol on the male rat reproductive system

Abstract: Background:Bisphenol A (BPA) and nonylphenol (NP) have harmful effects on the endocrine system of humans and animals.Aim:We sought to investigate the effect of three doses of BPA and NP on the reproductive parameters of rats.Materials and Methods:Adult Wistar male rats weighing 150–200 g were used for a consecutive 35-day study. BPA and NP were given as gavage in three doses (5, 25, and 125 μg/kg). At the end of the study, the rats were anesthetized and 2 ml blood sample was obtained from the auxiliary venous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…BPA chemical toxic effects are confirmed in adult rats, showing reduced testes and prostate gland weights, decreased serum testosterone levels, reduced diameter and thickness of seminiferous tubules, significantly thinner seminiferous epithelium and subsequent abnormal spermatogenesis in term of decreased sperm count and motility [25]. The authors postulate that in rats exposed to BPA there is a loss of structural integration in the gonadal compartment with the formation of gaps between germinal cells, as demonstrated previously in in vitro studies [32, 33].…”
Section: Bpa and Male Reproduction In Animal Modelsmentioning
confidence: 58%
“…BPA chemical toxic effects are confirmed in adult rats, showing reduced testes and prostate gland weights, decreased serum testosterone levels, reduced diameter and thickness of seminiferous tubules, significantly thinner seminiferous epithelium and subsequent abnormal spermatogenesis in term of decreased sperm count and motility [25]. The authors postulate that in rats exposed to BPA there is a loss of structural integration in the gonadal compartment with the formation of gaps between germinal cells, as demonstrated previously in in vitro studies [32, 33].…”
Section: Bpa and Male Reproduction In Animal Modelsmentioning
confidence: 58%
“…It is used in detergents, emulsifiers, and in several industries, for example in paints, pesticides, and household toiletries [7]. Studies have suggested that NP has deleterious effects on the endocrine [8], reproductive [9], immune [10], and nervous systems in animals and humans [11].…”
Section: Introductionmentioning
confidence: 99%
“…NP has been detected in human urine samples 10 and adipose tissues 11 . Studies have suggested that NP has deleterious effects on endocrine 12 , reproductive 13 , immune 14 , and nervous 15,16 systems in animals and humans.…”
Section: Introductionmentioning
confidence: 99%